PENAMBAHAN INULIN UMBI DAHLIA PADA PEMBUATAN ES KRIM - Dewi Pratiwi; Raswen Efendi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The objective of this research was to determine the effect of addition of dahlia tuber inulin on the physical, chemical, and sensory properties of ice cream. This study used a completely randomized design (CRD) with six treatments and three replications. The treatment in this study was the level of addition of inulin in ice cream. The levels of addition of inulin were E0 (without the addition of inulin dahlia tuber), E1 (addition of 1% inulin dahlia tuber), E2 (addition of 2% inulin dahlia tuber), E3 (addition of 3% inulin dahlia tuber), E4 (addition of 4% inulin dahlia tuber) and E5 (addition of 5% inulin dahlia tuber). The data obtained were analyzed statistically using analysis of variance (ANOVA). If F count is greater than or equal to F table then proceed with the DNMRT test at level 5%. The results of this study showed that the level of addition of dahlia tuber inulin in ice cream production had a significant effect (P<0.05) on overrun, melting time, crude fiber, and fat content.  This treatment also gave significantly different results (P<0.05) on a descriptive assessment of color, flavor, taste, and texture, as well as a hedonic assessment of the overall acceptance of ice cream. The best treatment for ice cream from this study was E4 with overrun 15.40%, melting time 11.04 minutes, fiber content 0.70%, fat content 5.72%, light brown color (score 3.47), mildly flavored milk (score 3.37), taste milk (score 3.63), and soft texture (score 3.63) and the overall assessment of ice cream favored by panelists (score 3.65).Keywords:inulin, dahlia tuber inulin, and ice cream.